1974
DOI: 10.1128/jb.117.3.1023-1034.1974
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-Induced Derepression of Tryptophan Biosynthesis in a Tryptophanyl-Transfer Ribonucleic Acid Synthetase Mutant of Bacillus subtilis

Abstract: A tryptophanyl-transfer ribonucleic acid (tRNA) synthetase (L-tryptophan:t-RNA ligase adenosine monophosphate, EC 6.1.1.2) mutant (trpSl) of Bacillus subtilis is derepressed for enzymes of the tryptophan biosynthetic pathway at temperatures which reduce the growth rate but still allow exponential growth. Derepression of anthranilate synthase in a tryptophan-supplemented medium (50 ,g/ml) is maximal at 36 C, and the differential rate of synthesis is 600to 2,000-fold greater than that of the wild-type strain or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

1974
1974
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…In tryptophan-dependent growth. The latter strain is deficient in tRNA Trp charging when grown at elevated tem-the comparable trpS1 temperature-sensitive strain the AT level with the wild-type rtpLP construct was elevated peratures (Steinberg, 1974;Sarsero et al, 2000b). The chromosomal at operon was deleted from both of these appreciably (Figure 3, compare lane 3 with lane 1).…”
mentioning
confidence: 93%
“…In tryptophan-dependent growth. The latter strain is deficient in tRNA Trp charging when grown at elevated tem-the comparable trpS1 temperature-sensitive strain the AT level with the wild-type rtpLP construct was elevated peratures (Steinberg, 1974;Sarsero et al, 2000b). The chromosomal at operon was deleted from both of these appreciably (Figure 3, compare lane 3 with lane 1).…”
mentioning
confidence: 93%
“…The regulation of the tryptophan operon ( trp ), mediated by the Trp repressor and transcriptional attenuation, has been widely studied in bacteria [ 35 ]. Bacillus subtilis harbors a temperature-sensitive tryptophanyl-tRNA synthetase where it was observed that at high temperatures, when the bacterium growth is reduced but not suppressed, the trp operon was induced [ 36 ]. This process is likely mediated by the reduced availability of the trp attenuator protein TRAP [ 37 , 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…A temperature-sensitive tryptophanyl-tRNA synthetase mutant of B. subtilis was recently isolated by Steinberg and Anagnostopoulos (25). They reported that at elevated temperatures both anthranilate synthase and tryptophan synthase-B were coordinately derepressed (24). The possibility that tryptophanmediated control ofhistidinol phosphate aminotransferase in these mutants was in some way altered from that resulting from tryptophan limitation was investigated.…”
Section: Resultsmentioning
confidence: 99%
“…At least two regulatory loci have been implicated in the control of tryptophan biosynthesis in B. subtilis (19,24). Steinberg (24) isolated a strain that had a temperature-sensitive tryptophanyl-tRNA synthetase.…”
Section: Resultsmentioning
confidence: 99%